Volume 4B: Combustion, Fuels and Emissions 2016
DOI: 10.1115/gt2016-57223
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Kinetic Models for Enhancing Gas Turbine Flexibility: Model Validation and Application

Abstract: In recent years, market trends towards higher power generation flexibility are driving gas turbine requirements of operation at stable conditions and below environmental emission guarantees over a wide range of operating conditions, such as load, and for changing fuels. In order to achieve these targets, engine components and operation concept need to be optimized to minimise emissions (e.g. CO, NOx) and combustion instabilities, as well as to maximize component lifetime. Therefore the combination of field exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The dimensionless time reduced is a measure for the burnout progression, ranging from reduced ¼ 0 (no burnout) to reduced ¼inf, while the first occurrence of complete burnout (CO concentration sufficiently close to its equilibrium) is reached at reduced ¼ 1 by definition. 2 The oxidation of CO leads thus to a decline of the initial value CO peak of equation ( 6) to its equilibrium CO equil by oxidation of ÁCO peak ¼ CO peak À CO equil with (reduced) time and slope…”
Section: Comentioning
confidence: 99%
See 3 more Smart Citations
“…The dimensionless time reduced is a measure for the burnout progression, ranging from reduced ¼ 0 (no burnout) to reduced ¼inf, while the first occurrence of complete burnout (CO concentration sufficiently close to its equilibrium) is reached at reduced ¼ 1 by definition. 2 The oxidation of CO leads thus to a decline of the initial value CO peak of equation ( 6) to its equilibrium CO equil by oxidation of ÁCO peak ¼ CO peak À CO equil with (reduced) time and slope…”
Section: Comentioning
confidence: 99%
“…More recently, Therkorn et al 17 assessed burner switch-off concepts for the auto-ignited sequential combustor in the GT24/GT26 gas turbine and successfully modeled its influence on CO emissions with a semiempirical model. Enriching this approach with accurate kinetics in a simple reactor model, Gu¨the et al 2 demonstrated the capability to capture the effect of fuel reactivity (i.e. hydrocarbon and hydrogen content) at lab and engine scale.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations